Knowledge mapping of ferroptosis in Parkinson’s disease: a bibliometric analysis: 2012–2023 - Li, Juanqin; Wang, Yanli; Huang, Jing; Gong, Daokai (Frontiers in Aging Neuroscience, 2024)
Background Ferroptosis is a crucial pathogenic mechanism in Parkinson’s disease, offering significant potential for pharmacological intervention. Despite its importance, the number of bibliometric analyses examining the relationship between ferroptosis and Parkinson’s disease remains limited. This study aims to elucidate the knowledge structure and primary research focuses within this field using various bibliometric tools search. Materials and methods We conducted a comprehensive literature son ferroptosis in Parkinson’s disease using the Web of Science Core Collection database. Bibliometric analyses and visualizations were performed with VOSviewer, examining the geographical and institutional distribution of publications, journal interconnections, and keyword prevalence. Furthermore, CiteSpace was used to visually explore and analyze journal interactions and citation dynamics. The bibliometrix R package facilitated the delineation of collaborative networks across different countries and the construction of visual network representations illustrating relationships among authors, keywords, and journals. Data visualization was further enhanced with Microsoft Office Excel 2021. Results Recently, there has been a significant increase in publications on ferroptosis, with China emerging as a leading contributor in this research area. Keyword analysis highlights the critical role of ferroptosis in the pathogenesis of Parkinson’s disease, identifying GPX4 as a key enzyme mitigating lipid peroxidation. This study also elucidates the connections and distinctions between ferroptosis and other cell death processes such as apoptosis, autophagy, and pyroptosis. Current research primarily focuses on immunotherapy, prognosis, oxidative stress, lipid peroxidation, and the tumor microenvironment. Conclusion This study provides a comprehensive initial analysis of the research landscape, identifying current focal points and potential future directions for ferroptosis research in Parkinson’s disease. The findings leverage a variety of bibliometric methodologies to offer valuable insights into this emerging field.